Democratization in post-Suharto Indonesia [ - Bèunte, Marco , 1970-; Ufen, Andreas , 1965- (London New York : Routledge, 2009)
Offers insights into the restructuring of core state institutions, the empowerment of Parliament, the slow and difficult evolution of the rule of law, and the transfer of power to locally elected regional governments in Indonesia. This book is suitable for scholars engaged in research on Indonesia and the politics of Southeast Asia
Description based on print version record
Includes bibliographical references and index
Keywords: Democracy -- Indonesia; Democratization -- Indonesia; Indonesia -- Politics and government -- 1998-